2022
DOI: 10.12912/27197050/152104
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Mine Waters Using Lime and Aluminum Hydroxochloride

Abstract: Analysis of the scientific and technical literature shows that there are quite a few methods of mine water processing. Reagent methods can be considered as the most promising and economically expedient. Mine waters are characterized by a high content of hardness ions and sulfates. The concentration of sulfates varies between 5-35 mg-eq/ dm 3 , hardness -10-40 mg-eq/dm 3 . It has been established that effective purification of water from sulfates can be achieved with the use of lime and 5/6 aluminum hydroxochlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, without prior chemical or ion exchange treatment, these membranes quickly lose their permeability due to salt deposition on their surface. Additionally, pretreating the water with aluminium hydroxychloride [3,4] or sodium hydroxyaluminate [5] results in the formation of precipitates that require disposal. While membrane regeneration is an effective solution, it is often prohibitively expensive, leading to the decision to replace the membranes entirely and resulting in a significant increase in the cost of water treatment.…”
Section: Analysis Of Previous Studiesmentioning
confidence: 99%
“…However, without prior chemical or ion exchange treatment, these membranes quickly lose their permeability due to salt deposition on their surface. Additionally, pretreating the water with aluminium hydroxychloride [3,4] or sodium hydroxyaluminate [5] results in the formation of precipitates that require disposal. While membrane regeneration is an effective solution, it is often prohibitively expensive, leading to the decision to replace the membranes entirely and resulting in a significant increase in the cost of water treatment.…”
Section: Analysis Of Previous Studiesmentioning
confidence: 99%
“…All this together makes the technology expensive and more energyconsuming, unlike liming when using red mud. When using 5/6 AHC and liming of water for purification of mineralized waters with an initial concentration of sulfates of 16 mg-eq/dm 3 , it was shown that the degree of purification reaches 65 % [47]. It was shown that the degree of purification reaches 75 %, when using red sludge and liming of water for purification of mineralized waters with an initial concentration of sulfates of 20 mg-eq/dm 3 .…”
Section: Fig3 the Dependence Of The Residual Concentration Of Sulfate...mentioning
confidence: 99%
“…To mitigate the negative impact of mine water discharge, various purification methods and water treatment schemes are used, including bio-purification, ion exchange, coagulation, disinfection, oxidation, settling, sorption, filtration, and flotation [3]. Despite hundreds of combinations of these methods being proposed, only a small number of them are considered to be efficient for industrial use 2 [4,5]. This is because some treatment technologies (biochemical and coagulation) do not meet modern requirements for treatment quality and produce significant amounts of sediments, which require large areas for storage and disposal.…”
Section: Introductionmentioning
confidence: 99%